A GUIDE TO THE PROJECT MANAGEMENT BODY OF KNOWLEDGE : ( PMBOK Guide). (Project Management Institute)
Reflects the collaboration and knowledge of working project managers, providing the fundamentals of project management as they apply to a wide range of projects. This internationally recognized standard provides the essential tools to practice project